«El camino es la vida» 1 : transgresiones de género y edad en Ladies of Steel - Dra. María Isabel MENÉNDEZ MENÉNDEZ (Fonseca, Journal of Communication, 2023)
Pamela Tola’s Ladies of Steel was the most watched movie of 2020 in Finland, and it was nominated as Best Comedy in the European Film Awards. It is a road movie whose protagonists are three women in their seventies, and which breaks with the ageist paradigm and with gender stereotypes. Through a qualitative approach and developing a feminist analysis, this article looks into the variables of difference present in road movies with female protagonists, with special interest in their representation of age